Evaluating The Accuracy Of Fine Needle Aspiration Cytology Of Breast Lesion Using International Academy Of Cytology Yokohama System: A Study In Eastern Nepal - Sedhain, Sapana; Bhattarai, Soorya; Sinha, Amrita; Kafle, Neeta; Singh, Mrinalini (Birat Journal of Health Sciences, 2024)
Introduction: Breast Carcinoma is the most common cancer in females worldwide. In developing countries, it is the most common cause of cancer-related deaths in women. The IAC Yokohama breast FNAB reporting system was developed as a multidisciplinary approach to have a standardized and structured report, for improvement in interpretation of breast cytology. Objectives: This study aims to classify Fine needle aspiration cytology of breast lesion according to the IAC Yokohama system and assess diagnostic accuracy of different categories. Methodology: This was a hospital based prospective cross-sectional study conducted in the Department of Pathology, Birat Medical College Teaching Hospital from August 2022 to May 2023. All patient with Breast lesions who underwent FNAB were included in the study. FNAB were categorized using IAC Yokohama reporting system. Considering histopathology as a final diagnosis sensitivity, specificity, PPV, NPV, Diagnostic accuracy and Risk of Malignancy were calculated. Results: One hundred and fifty-six patients underwent FNAB during the study period and 124 patients had histopathological reports available. Frequency of FNAB using Yokohama System were: Inadequate -1.9%, Benign- 59%, Atypical 14.7%, Suspicious- 11.5%, Malignant- 12.8% respectively. The Risk of Malignancy for each category were 33%, 1.51%, 22.22%, 94.11% and 100% respectively. Maximum sensitivity (97.56%) and NPV (98.48%) was achieved when considering Atypical, Suspicious for Malignancy and Malignant category as Positive. Whereas highest specificity (100%) and PPV (100%) was achieved when considering only the Malignant category as Positive. Conclusion: The IAC Yokohama System is a standard tool for diagnosing Breast FNAB with greater reproducibility and maximum diagnostic accuracy.